2018
DOI: 10.1080/19415257.2018.1490917
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s more than a prop’: Professional development session strategies as sources of teachers’ self-efficacy and motivation to teach outside the classroom

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The added value of this is knowledge of which sources are relatively the most important when the impact of other sources is controlled for. Often the focus has been primarily on mastery experiences (Glackin, 2018). While valuable, because its importance was also corroborated in our study, this should not be the sole focus, as we found that positive emotions also influenced self-efficacy.…”
Section: Implications For Researchsupporting
confidence: 72%
See 1 more Smart Citation
“…The added value of this is knowledge of which sources are relatively the most important when the impact of other sources is controlled for. Often the focus has been primarily on mastery experiences (Glackin, 2018). While valuable, because its importance was also corroborated in our study, this should not be the sole focus, as we found that positive emotions also influenced self-efficacy.…”
Section: Implications For Researchsupporting
confidence: 72%
“…More specifically, there are hardly any studies that have investigated all sources simultaneously and have quantitatively assessed the degree to which they make an independent contribution to self-efficacy (Morris, Usher & Chen, 2017). Hence, there is a need for more research that includes all sources (Glackin, 2018). Second, there is a lack of research into the fourth source of self-efficacy: physiological and affective states (Morris & Usher, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, for in-service teachers, the roles of non-cognitive skills are recognised. This is evident with a large number of professional development programs designed to enhance teachers' non-cognitive skills such as self-efficacy (Stevens et al, 2013;Glackin, 2019), motivation (Cheon et al, 2018) and adaptability (Parsons et al, 2016). The implicit nature of the 6 th standard of the APST, engage in professional learning, allows educational practitioners to develop their non-cognitive skills as they are required to 'engage in professional learning and improve practice' (AITSL, 2011b, p. 20) and 'apply professional learning and improve student learning' (AITSL, 2011b, p. 21).…”
Section: Critical Review Of the Australian Professional Standards For …mentioning
confidence: 99%
“…Another example of the student hat structure is a study on an outdoor teaching PD for science teachers (Glackin, 2019). This study calls the structure “simulated modeling,” but describes how that involved engaging teachers in the outdoor activities they might facilitate for students so that teachers could experience what it felt like from the student perspective to learn science outdoors.…”
Section: Defining the Student Hat In Teacher Professonal Developmentmentioning
confidence: 99%